Association of metabolic syndrome and insulin resistance in papulosquamous diseases - Hosthota, Abhineetha; U., Ishwarya; Thampi, Anila Sara; R., Supriya; Kavya , Chaganam; B. C., Chandan; Venumbaka , Bhavana (International Journal of Research in Dermatology, 2023)
Background: Metabolic syndrome (MetS), insulin resistance (IR) and papulosquamous diseases with shared pathophysiology leads to conglomeration of risk factors of non-communicable diseases like cardiovascular disease (CVD) and type 2 diabetes (T2D) causing high mortality worldwide. The objective is to study the association of MetS and IR in papulosquamous diseases. Methods: It is a hospital-based case-control study conducted on 200 age-sex matched cases and controls with consent. Subjects were administered a pre-validated questionnaire, diagnosis of papulosquamous diseases was based on clinical examination and skin biopsy. MetS was diagnosed based on national cholesterol education program's- adult treatment plan iii with Asian modification for abdominal circumference criteria. Fasting serum insulin levels (FI) was used as a surrogate marker of IR. Results: Mean serum HDL- C level was low and statistically significant (p=0.017). Mean fasting plasma glucose level was significantly higher in patients (p=0.008). Mean FI level was significant between cases and controls (p=0.013). IR was found in 76% of cases which was significantly higher than in controls (p<0.05). IR was highest in psoriasis 29% followed by LP 22%, PRP 19%, and LS 6% which was statistically significant (p<0.05). MetS was mostly found in psoriasis (17%), LP (9%) and least in PRP, LS. Conclusions: This study intends clinicians to do periodic MetS and IR evaluation in papulosquamous diseases. Thus, subclinical cases of non-communicable diseases can be detected and potential co-morbidities can be prevented.